Electroacupuncture for Functional Constipation: A Multicenter, Randomized, Control Trial. (31st January 2017) - Wu, Xiao; Zheng, Cuihong; Xu, Xiaohu; Ding, Pei; Xiong, Fan; Tian, Man; Wang, Ying; Dong, Haoxu; Zhang, Mingmin; Wang, Wei; Xu, Shabei; Xie, Minjie; et al.
Abstract : Background and Aim . To investigate the efficacy and safety of electroacupuncture (EA) with different current intensities for functional constipation (FC) and to assess whether the effects of EA with different current intensities are superior to the mosapride. Methods . Patients with FC were randomly divided into low current intensity group (LCI), high current intensity group (HCI), and mosapride group (MC). The primary outcome was three or more spontaneous bowel movements (SBMs) per week and an increase of one or more SBMs from baseline during at least 3 of the 4 weeks. Results . The primary outcome was reached by 53.45%, 66.15%, and 52.24% of the patients who received LCI, HCI, and mosapride, respectively. EA can significantly improve the weekly SBMs and stool consistency and reduce straining severity (p < 0.0001, all). HCI improved the quality of life better than mosapride (p < 0.05 ) and reduced the proportion of severe constipation more than LCI and mosapride (p < 0.05, both). Conclusions . EA is effective and safe at both current intensities for FC; therapeutic effects of LCI and HCI are not superior to mosapride. EA is superior to mosapride in improving patients' life quality and satisfaction level of treatment; EA has fewer adverse events than mosapride.